Chronophysiology of Rat Wistar under Extracts from Khaya Senegalensis - ZOHOUN, Loica; MICHODJEHOUN, VIOUTOU LAETITIA; HOUNDEFFO, TIBURCE ALIHONOU ADIHOU GNÉTOGON; KANGBETO, Roland; GBENOU, JUDITH ANNE VALERIE; SEZAN, ALPHONSE (My University, 2018)
Generally in Africa and particularly in Benin, the population is increasingly confronted with several pathologies such as diabetes, colds, chest pain, gastric disorders, malaria, bechia, colic and so on. Although modern medicine is well developed, this population for the treatment of these diseases uses traditional medicine because of their low purchasing power. The frequent use of these medicinal plants by traditional healers and the satisfactory results which follow in certain cases has led us to carry out a more thorough reflection on Khaya senegalensis in order to relate the use made by traditional healers and scientific evidence. The present work was carried out in order to evaluate the bioactivity of the ethanol extract of the Khaya senegalensis barks according to the time of day in the Wistar rat. After phytochemical screening of the extracts, glycaemia, triglyceridemia, total cholesterol, transaminases (ASAT and ALAT) and urea were measured spectrophotometrically in three (03) batches of three (03) Wistar rats each. Lots 2 and 3 received oral doses of 2.5 mg / kg and 5 mg / kg body weight of the extracts, respectively, at 10 am during the day. Control batch 1 received distilled water in place of the extract. The results of phytochemical screening revealed the presence of polyphenolic compounds (gallic tannins, catechic or condensed tannins, anthocyanins, and leuco-anthocyanins), flavonoids, mucilages of reducing compounds, alkaloids, certain anthracene derivatives (Free anthracenics, O-heterosides), steroids, and quinone derivatives. There was a significant decrease (p ˂ 0.05) in the blood glucose level 12h after treatment with the extract. Batch 3 which received 5 mg / kg by weight had a lower rate than the batch received 2.5 mg / kg body weight. Triglyceridemia, cholesterol, transaminases and urea did not differ significantly from the control batch (p <0.05), but these values are high compared to the normal values of wistar rats and are due to l Feeding of these rats. The long-term use of the ethanolic extract of Khaya senegalensis bark could compromise liver and kidney function and inhibit apoptosis, that is, can induce cancer in the wistar rat.
Keywords: Khaya senegalensis; Bark; Extracts; Biological rhythm; Biochemical parameters